Effect of Sintering Temperature on Electrical Conductivity, Hardness and Friction Properties of Cu/MgB2 Composites - Yang, Qing; Huang, Jinyang; Zou, Juntao; Fu, Huitan (Asian Journal of Chemistry, 2014)
The Cu/MgB2 composites with MgB2 content of 10, 20, 30 vol. % were fabricated by pressing-sintering at 800 ºC and repressing-resintering at 900 ºC. The effect of sintering temperature on the properties of Cu/MgB2 composites including the relative density, hardness, friction coefficient and electrical conductivity was investigated. The results showed that the decrease of sintering temperature from 900 to 800 ºC contributed to the increase of relative density and hardness of Cu/MgB2 composites with MgB2 content lower than 30 vol. % and contributed to the increase of friction coefficient and electrical conductively of Cu-20 % MgB2 composite. The properties of Cu/MgB2 composites sintered at 800 ºC, which were lower than those sintered at 900 ºC, were increased and approximated to those sintered at 900 ºC after the repressing-resintering process.